Still time to perform intestinal revascularization in patients with acute mesenteric ischemia with peritonitis: An analysis of bowel viability in resections. (May 2020) - Hayashi, Kentaro; Hayashi, Ken; Narita, Makoto; Tsunoda, Akira; Kusanagi, Hiroshi
Objective: Acute mesenteric ischemia is often fatal, and many survivors develop short bowel syndrome. To avoid massive bowel resection, revascularization is recommended for acute mesenteric ischemia patients. However, whether acute mesenteric ischemia patients with clinical peritonitis can be revascularized remains uncertain. Therefore, this study aimed to evaluate the histopathological potential reversibility of resected bowel in acute mesenteric ischemia patients with peritonitis. Methods: We retrospectively reviewed the medical records of acute mesenteric ischemia patients treated at the Kameda Medical Center between January 2001 and March 2015. Pathological evaluation regarding bowel resection was performed. Patients with and without peritonitis were compared. The primary outcome was the proportion of patients with reversible or irreversible ischemia. Patients with reversible and irreversible ischemia were characterized. Results: Of 41 patients, 17 underwent laparotomy, 6 endovascular surgery, and 18 palliative care. Among 23 patients receiving curative treatment, 7 had peritonitis and 13 did not. Seven patients of each group received bowel resection, but 85.7% of those with peritonitis had reversible ischemia. We categorized patients with ischemia into reversible and irreversible groups. The median time between symptom onset and diagnosis in the reversible group was >27 h. Systemic inflammatory response syndrome was found in 72.2% and 66.7% of the reversible and irreversible groups, respectively. Conclusion: Acute mesenteric ischemia patients with clinical peritoneal signs may have potentially reversible ischemia. As a result, revascularization should be considered, even in the case of peritonitis.